2020
DOI: 10.31557/apjcp.2020.21.8.2259
|View full text |Cite
|
Sign up to set email alerts
|

Urine Neutrophil Gelatinase-Associated Lipocalin a Possible Diagnostic Marker for Egyptian Hepatocellular Carcinoma Patients

Abstract: Background: Most effective method for reducing mortality from hepatocellular carcinoma (HCC) is early diagnosis. Despite its lack of adequate sensitivity, ultrasound is considered fundamental for HCC screening. Aim: to evaluate urinary neutrophil gelatinase-associated lipocalin (NGAL) as non-invasive marker for HCC diagnosis in Egyptian patients. Methods: One hundred and twenty patients were divided into three groups (40 patients each): patients with chronic viral hepatitis (HCV or HBV), cirrhotic patients and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…Interestingly, the expression of both LNC2 and MMP9 genes was increased in 16 tumor types, demonstrating their involvement in tumor development. This result was consistent with those reported in the literature for several tumors, including BLCA ( Ricci et al, 2015 ; Candido et al, 2016b ), CESC ( Li et al, 2012 ), CHOL ( Leelawat et al, 2011 ; Nair et al, 2018 ; Li et al, 2019 ), ESCA ( Zhang et al, 2007 ), HNSC ( Ruokolainen et al, 2005 ; Hiromoto et al, 2011 ; Stanciu et al, 2016 ; Verma et al, 2017 ), KIRP ( Cho et al, 2003 ; Zhang et al, 2015 ), LIHC ( Chen et al, 2012 ; Abdelsameea et al, 2020 ), LUAD ( Ruiz-Morales et al, 2015 ), OV ( Cho and Kim, 2009 ; Gupta et al, 2022 ); PAAD ( Kaur et al, 2013 ), STAD ( Du et al, 2011 ), UCEC ( Cymbaluk-Płoska et al, 2017 ), COAD ( Yang et al, 2014 ; Ozemir et al, 2016 ; Liang and Chang, 2018 ), LUSC ( Lee et al, 2015 ), PRAD ( Ma et al, 2017 ; Muşlu et al, 2017 ; Ulusoy et al, 2021 ), READ ( Zhang et al, 2009 ; Annaházi et al, 2016 ), and THCA ( Barresi et al, 2012 ; Liu et al, 2019 ; Xu et al, 2019 ).…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, the expression of both LNC2 and MMP9 genes was increased in 16 tumor types, demonstrating their involvement in tumor development. This result was consistent with those reported in the literature for several tumors, including BLCA ( Ricci et al, 2015 ; Candido et al, 2016b ), CESC ( Li et al, 2012 ), CHOL ( Leelawat et al, 2011 ; Nair et al, 2018 ; Li et al, 2019 ), ESCA ( Zhang et al, 2007 ), HNSC ( Ruokolainen et al, 2005 ; Hiromoto et al, 2011 ; Stanciu et al, 2016 ; Verma et al, 2017 ), KIRP ( Cho et al, 2003 ; Zhang et al, 2015 ), LIHC ( Chen et al, 2012 ; Abdelsameea et al, 2020 ), LUAD ( Ruiz-Morales et al, 2015 ), OV ( Cho and Kim, 2009 ; Gupta et al, 2022 ); PAAD ( Kaur et al, 2013 ), STAD ( Du et al, 2011 ), UCEC ( Cymbaluk-Płoska et al, 2017 ), COAD ( Yang et al, 2014 ; Ozemir et al, 2016 ; Liang and Chang, 2018 ), LUSC ( Lee et al, 2015 ), PRAD ( Ma et al, 2017 ; Muşlu et al, 2017 ; Ulusoy et al, 2021 ), READ ( Zhang et al, 2009 ; Annaházi et al, 2016 ), and THCA ( Barresi et al, 2012 ; Liu et al, 2019 ; Xu et al, 2019 ).…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, they found that LCN2 levels are able to discriminate between HCC and liver cirrhosis subjects, and they also proved that LCN2 levels are not suitable to distinguish between early and late HCC. This goes along with an Egyptian study showing how even urine LCN2 can serve as a marker in HCC diagnosis [91]. In the respective study, LCN2 levels were significantly elevated in patients with HCC in contrast to the control, cirrhotic patients, and patients with chronic hepatitis.…”
Section: Lcn2 and Its Significance In Hepatocellular Carcinomamentioning
confidence: 66%
“…Although we did not search for hepatocellular carcinoma cases in this study, this is a very interesting report that also explores the mechanism behind the elevated levels. 20 Oikonomou et al . reported that NGAL is elevated in active IBD and correlates with established inflammatory markers and disease activity.…”
Section: Discussionmentioning
confidence: 99%